International migration and crisis : transition toward a new migratory phase - Jardón Hernández, Ana Elizabeth (Springer, 2016)
This book presents an analysis of the various transformation processes at work in the international migratory dynamic of Mexicans as a consequence of the 2008 international economic crisis and the implementation of an increasingly strict American migration policy. Employing a methodology that combines qualitative and quantitative tools, the main findings of this work indicate that the international migration of Mexicans is moving towards a new phase, an era of "contraction and disengagement" that is characterized by the confluence of multiple changes with repercussions on the functioning of international migration as a socioeconomic strategy at the family and migrant community levels. .
Keywords: Emigration and immigration -- Social aspects.; elektronické knihy; electronic books